Cerebral topographies of perceived and felt emotions - Saarimaki, Heini; Nummenmaa, Lauri; Volynets, Sofia; Santavirta, Severi; Aksiuto, Anna; Sams, Mikko; Jaaskelainen, Iiro P.; Lahnakoski, Juha M. (MIT PRESS, 2026)
Emotions modulate behavioral priorities based on exteroceptive and interoceptive inputs, and the related central and peripheral changes may be experienced subjectively. Yet, it remains unresolved whether the perceptual and subjectively felt components of the emotion processes rely on shared brain mechanisms. We applied functional magnetic resonance imaging, a rich set of emotional movies, and high-dimensional, continuous ratings of perceived and felt emotions in the movies to investigate their cerebral organization. Emotions evoked during natural movie scene perception were represented in the brain across numerous spatial scales and patterns. Perceived and felt emotions generalized both between individuals and between different stimuli depicting the same emotions. The neural affective space demonstrated an anatomical gradient from emotion-general responses in polysensory areas and default mode regions to more emotion-specific discrete processing in subcortical regions. Differences in brain activation during felt and perceived emotions suggest that temporoparietal areas and precuneus have a key role in evaluating the affective value of the sensory input, and subjective emotional state generation is associated with further and significantly stronger recruitment of the temporoparietal junction, anterior prefrontal cortices, cerebellum, and thalamus. These data reveal the similarities and differences of domain-general and emotion-specific affect networks in the brain during a wide range of perceived and felt emotions.